TEKNIK PERSUASI NABI MUHAMMAD KEPADA KAUM ANSHAR DALAM PEMBAGIAN GHANIMAH PERANG HUNAIN - Yudi Asmara Harianto (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2022)
Da'wah to congregants who have negative prejudices is not an easy thing. The Prophet Muhammad experienced this condition during the distribution of the Hunain war ghanimah. The Ansar had a negative prejudice that the Prophet had acted unjustly. This paper aims to describe the persuasive da'wah communication techniques used by the Prophet in this incident. The method used in this paper is a literature study. The results of analysis show that the Prophet Muhammad used several persuasive da'wah communication techniques, namely yes response, say it with flowers, and pay-off. There is an interesting finding that in influencing and changing Ansar's attitude the Prophet Muhammad did not put words of invitation at the core of his message, but used question words. The persuasive da'wah techniques used by the Prophet Muhammad are useful as a reference for modern preachers in dealing with conditions of crisis of trust.